New Conceptualizations of Practice: Common Principles in Three Paradigms Suggest New Concepts for Training - Schmidt, Richard A.; Bjork, Robert A. (Psychological Science, 1992)
We argue herein that typical training procedures are far from optimal. The goat of training in real-world settings is, or should be, to support two aspects of posttraining performance: (a) the level of performance in the long term and (b) the capability to transfer that training to related tasks and altered contexts. The implicit or explicit assumption of those persons responsible for training is that the procedures that enhance performance and speed improvement during training will necessarily achieve these two goals. However, a variety of experiments on motor and verbal learning indicate that this assumption is often incorrect. Manipulations that maximize performance during training can be detrimental in the long term; conversely, manipulations that degrade the speed of acquisition can support the long-term goals of training. The fact that there are parallel findings in the motor and verbal domains suggests that principles of considerable generality can be deduced to upgrade training procedures.